2021
DOI: 10.1186/s13054-021-03534-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical outcomes between nurse practitioner and registrar-led medical emergency teams: a propensity-matched analysis

Abstract: Objective Medical emergency teams (MET) are mostly led by physicians. Some hospitals are currently using nurse practitioners (NP) to lead MET calls. These are no studies comparing clinical outcomes between these two care models. To determine whether NP-led MET calls are associated with lower risk of acute patient deterioration, when compared to intensive care (ICU) registrar (ICUR)-led MET calls. Methods The composite primary outcome included recur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Recent research on APPs in critical care often focused on the evaluation of clinical patient-related outcomes and performances of these APPs in conjunction with a coordinating medical specialist. (2)(3)(4) In this study the non-technical skills of APPs and residents as leaders of a RRT were assessed without this additional consultation. APPs performed better than residents in several subcategories and omitted overall less predefined critical steps.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on APPs in critical care often focused on the evaluation of clinical patient-related outcomes and performances of these APPs in conjunction with a coordinating medical specialist. (2)(3)(4) In this study the non-technical skills of APPs and residents as leaders of a RRT were assessed without this additional consultation. APPs performed better than residents in several subcategories and omitted overall less predefined critical steps.…”
Section: Discussionmentioning
confidence: 99%
“…This study compared an APP-led rapid response team with a resident-led rapid response team. This study found no differences between the groups except for a shorter in-hospital stay of the patients visited by the APP-led group but after propensity matching [ 13 ]. The study mainly focused on patient outcomes and less on process outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, so far, an optimal composition and implementation of a rapid response team has not yet been established [ 8 , 19 ]. This fact and the lack of validated measurement tools except for the MAELOR tool probably explains why the literature reports different success rates and struggles with aligning outcome data when reporting on the performance of rapid response teams [ 3 , 8 , 13 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the moment, the optimal composition of an RRT is not yet known; the evaluation of rapid response teams emphasizes experience rather than a certain composition, although involvement of intensive care professionals may be beneficial [ 13 , 14 , 15 ]. A recent study using propensity score matching found that the participation of an APP in an RRT resulted in a decreased length of hospital stay [ 16 ]. Moreover, a recent study showed that APPs often provide direct additional value compared to a physician, as it measured process-related outcomes of APPs in a simulated rapid response team environment and showed that an APP might perform better than a medical resident (MR) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%